Gods and Talking Animals: the Pan-Cultural Recall Advantage of Supernatural Agent Concepts - Gregory, Justin P. (Journal of cognition and culture, 2019)
Supernatural agent concepts are regarded as a defining trait of religion. The interaction of the minimally counterintuitive (MCI) mnemonic effect and the hypersensitive agency detection device (HADD) may be employed to explain the universal presence of concepts of gods and deities. Using the measure of free-recall, a broad model of cultural transmission investigated this pan-cultural transmission bias with a large age-representative sample (3 to 86 years; N = 764) in UK and China. Results were analyzed by four-way mixed ANOVA considering counterintuitiveness, familiarity, ontological category, and delay, and with age as a covariate. A significant interaction of counterintuitiveness × HADD was found for both UK and China samples. These findings support assertions that supernatural agent concepts are more easily transmitted than other concepts because the present study finds that concepts similar to supernatural agents were more readily recalled.